The trans- pacific partnership as a strategy to contain China - Amaral, Gabriela Granço do (2013)
This paper aims to discuss the relationship between the United States and China in Asia Pacific. The analysis argues about the U.S. entry in the Trans-Pacific Partnership (TPP), which started in 2008. The complex relationship between these countries makes necessary the discuss about the economic interdependence between them, the strategies for Chinese foreign policy and the American interests in free trade treaties that involve the region. Thus, there is a panorama of perspectives that can be expected in the Sino-US relations in the coming years.